Agroforestry Management System Case Study: Mount Elgon in Mbale - Betty Nambozo (Uganda Christian University, 2025)
Effective agroforestry management is essential for optimizing land use, enhancing biodiversity, and improving agricultural productivity. Traditional management methods often lack the integration of real-time data and advanced analytics, which can limit their effectiveness. To address these limitations, my project focuses on the development and implementation of an Agroforestry Management System designed to enhance decision-making and operational efficiency. The primary objective of this research is to create a comprehensive, user-friendly platform that integrates real-time data collection, advanced analytics and intuitive management tools to support sustainable agroforestry practices. Utilizing an agile research methodology, my approach involves iterative development and continuous stakeholder feedback to refine the system's features and functionality. Data collection techniques, including field observations and user surveys, provide valuable insights into the needs and challenges faced by agroforestry practitioners. Preliminary results indicate that the Agroforestry Management System significantly improves the management of agroforestry practices, with users reporting enhanced decision-making capabilities and increased operational efficiency. This research aims to contribute to the advancement of agroforestry management by providing a modern, data-driven solution that supports sustainable land use and environmental stewardship. In conclusion, the findings from this study will offer valuable insights for stakeholders seeking to implement or improve agroforestry management practices, ultimately fostering more sustainable and productive agroforestry systems.